A Tunable Dual-Band Metamaterial Filter Based on the Coupling Between Two Crossed SRRs - Zhijun Qiao; Xuchao Pan; Fan Zhang; Jianchun Xu (IEEE Photonics Journal, 2021)
A tunable dual-band metamaterial filter based on crossed split-ring resonators is numerically and experimentally demonstrated. The proposed tunable metamaterial filter consists of two same metal split rings with different angles. Based on the cross-coupling between these two split rings, two stopbands are generated. Moreover, the operating frequency of the two stopbands can be tuned by changing the angle between the two split rings. In the context of numerical results, surface current distributions and electric field distributions were employed to analyze the basic principle, and the experiments were performed to demonstrate the practical effect. All results verified the tunable characteristics of the proposed metamaterial filter. This design proposes a new tunable metamaterial filter through the angle rotation.